Reading the Mind in the Eyes of Children Test (RME-C-T): Development and Validation of a Complex Emotion Recognition Test - Pahnke, Rike; Mau-Moeller, Anett; Hamm, Alfons O.; Lischke, Alexander (Frontiers in Psychiatry, 2020)
Much research has been devoted to the development of emotion recognition tests that can be used to investigate how individuals identify and discriminate emotional expressions of other individuals. One of the most prominent emotion recognition tests, is the Reading the Mind in the Eyes Test (RME-T). The original RME-T has been widely used to investigate how individuals recognize complex emotional expressions from the eye region of adult faces. However, the RME-T can only be used to investigate inter-individual differences in complex emotion recognition during the processing of adult faces. To extend its usefulness, we developed a modified version of the RME-T, the Reading the Mind in the Eyes of Children Test (RME-C-T). The RME-C-T can be used to investigate how individuals recognize complex emotional expressions from the eye region of child faces. However, the validity of the RME-C-T has not been evaluated yet. We, thus, administered the RME-C-T together with the RME-T to a sample of healthy adult participants (n = 119). The Interpersonal Reactivity Index (IRI) and the Toronto Alexithymia Scale (TAS) were also administered. Participants’ RME-C-T performance correlated with participants’ RME-T performance, implying that the RME-C-T measures similar emotion recognition abilities as the RME-T. Participants’ RME-C-T performance also correlated with participants’ IRI and TAS scores, indicating that these emotion recognition abilities are affected by empathetic and alexithymic traits. Moreover, participants’ RME-C-T performance differed between participants with high and low TAS scores, suggesting that the RME-C-T is sensitive enough to detect impairments in these emotion recognition abilities. The RME-C-T, thus, turned out to be a valid measure of inter-individual differences in complex emotion recognition during the processing of child faces.